Risk Mitigation Analysis on Illegal Online Loans Based on DSN MUI Fatwa Number 117/DSN/MUI/II/2018 (Study Case in Maguwoharjo Village) - Rahma Yudi Astuti; Malihatin (Universitas Darussalam Gontor, 2024)
The rapid development of financial technology has emerged various illegal online applications that provide convenience in lending and borrowing transactions more simply and quickly in the application process, but due to the many risks that occur such as defaults by borrowers and terror carried out by debt collectors make losses to the public. This study aims to analyze the risk mitigation of illegal online loans based on DSN MUI fatwa Number 117 / DSNMUI / II / 2018. The method used in the research is descriptive qualitative with case studies using snowball sampling with a unit of analysis that focuses on people and activities, namely individuals who have made illegal online loans. The informants in this study are 6 (six) people who use illegal online loan applications in Maguwoharjo Village, Yogyakarta Special Region. The type of data used is primary data supported by secondary data collected and data collection techniques using interviews and documentation. The results of this study show that risk mitigation has been carried out by every individual who makes illegal online loan transactions, namely receiving, reducing, and transferring to minimize the risk that occurs. Online lending is allowed. The most crucial thing in its application is that it does not conflict with sharia principles, including usury, gharar, maysir, tadlis, dharar, zhulm, and haram. Keywords: Risk mitigation, Illegal online loans, fatwa DSN MUI Nomor 117/DSNMUI/II/2018